Brain-derived neurotrophic factor (BDNF) has direct anti-inflammatory effects on microglia - Charlton, Tryston; Prowse, Natalie; McFee, Ashley; Heiratifar, Noora; Fortin, Teresa; Paquette, Carley; Hayley, Shawn (Frontiers in Cellular Neuroscience, 2023)
Microglia are the primary immunocompetent cells that protect the brain from environmental stressors, but can also be driven to release pro-inflammatory cytokines and induce a cytotoxic environment. Brain-derived neurotrophic factor (BDNF) is important for the regulation of plasticity, synapse formation, and general neuronal health. Yet, little is known about how BDNF impacts microglial activity. We hypothesized that BDNF would have a direct modulatory effect on primary cortical (Postnatal Day 1-3: P1-3) microglia and (Embryonic Day 16: E16) neuronal cultures in the context of a bacterial endotoxin. To this end, we found that a BDNF treatment following LPS-induced inflammation had a marked anti-inflammatory effect, reversing the release of both IL-6 and TNF-α in cortical primary microglia. This modulatory effect was transferrable to cortical primary neurons, such that LPS-activated microglial media was able produce an inflammatory effect when added to a separate neuronal culture, and again, BDNF priming attenuated this effect. BDNF also reversed the overall cytotoxic impact of LPS exposure in microglia. We speculate that BDNF can directly play a role in regulating microglia state and hence, influence microglia-neuron interactions.